2006
DOI: 10.1515/cclm.2006.192
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels and the expression of estrogen and progesterone receptors in breast cancer patients

Abstract: IL-1ra and IL-8 concentrations in serum, together with a lack of estrogen and progesterone receptors in tumor cells, in breast cancer patients older than 50 years could represent additional predictive factors for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…Similarly to our results, a previous study revealed that IL-1Ra levels were higher in patients with thyroid cancer (15). In normal cells, IL-1 secretion is mediated via inflammatory stimulation or cytokines, whereas tumor cells synthesize and secrete IL-1 through an autocrine mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly to our results, a previous study revealed that IL-1Ra levels were higher in patients with thyroid cancer (15). In normal cells, IL-1 secretion is mediated via inflammatory stimulation or cytokines, whereas tumor cells synthesize and secrete IL-1 through an autocrine mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation is frequently investigated in the etiology of different cancer types, including thyroid cancer. The immune system is hyperactive in Hashimoto's thyroiditis, and an association between this disease and thyroid cancer has been reported (15).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum levels of IL-1β correlate with breast cancer recurrence (Mettler et al, 2004). IL-1RA levels are higher in older breast cancer patients whose cancer lack estrogen receptors (Fuksiewicz et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Although there are several markers of disease that are associated with inflammation in breast cancer (Fuksiewicz et al, 2006), few studies have prospectively examined disease and treatment factors that might be related to change in inflammation in response to chemotherapy for breast cancer. Kummel et al (Kummel et al, 2006) examined circulating levels of VEGF (VEGF-A) and VEGF-D (a lymphangiogenic growth factor) (Yamazaki and Morita, 2006), prior to and following adjuvant chemotherapy in patients with positive node breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Strieter et al 50 found that IL-8 could promote corneal neovascularization in rabbits. Afterward, the function of IL-8 in tumor development received comprehensive attention, and its effect on promoting tumor angiogenesis was 54 Arenberg et al's 55 study confirmed that inhibiting the expression of IL-8 in SCID mice could reduce the incidence of non-small-cell lung cancer. High expression of IL-8 is closely related to the development of non-small-cell lung cancer; therefore, IL-8 can be used as a biochemical indicator for patients with non-small-cell lung cancer after prognosis.…”
Section: Immunohistochemistrymentioning
confidence: 99%